In vitro Evaluation of Antioxidant Potential of Leaves of Opuntia dillenii Haw. (Stamford Journal of Pharmaceutical Sciences, 2010)
Antioxidant potential of the 80% methanol extract of the leaves of Opuntia dillenii was evaluated using 1, 1-diphenyl, 2-picryl hydrazyl (DPPH) and nitric oxide radical scavenging, reducing power, total phenol and total flavonoid content determination assays. Preliminary phytochemical screening of the extract was also carried out, which revealed that the extract possesses flavonoids, steroids, alkaloids and tannins. The extract showed significant antioxidant activities in all antioxidant assays compared to the reference antioxidant in a dose dependent manner. In DPPH radical scavenging activity, the IC50 value of the crude extract was found to be 15.71μg/mL while the IC50 value for the reference ascorbic acid was 10.84 μg/mL. Again, the extract showed remarkable nitric oxide scavenging potential and good reducing power. Moreover, the methanol extract was found to contain high amount of phenols and flavonoids, expressed as gallic acid and rutin equivalents respectively. Based on the findings of the present study, we conclude that the methanol extract of the leaves of O. dillenii possesses remarkable antioxidant potential which may be attributed to the high amount of phenols and flavonoids present in the extract. Key Words: Opuntia dillenii; Antioxidant; Reactive oxygen species; DPPH; Nitric oxide radical DOI: 10.3329/sjps.v2i1.5811Stamford Journal of Pharmaceutical Sciences Vol.2(1) 2009: 22-26